Immune strategies using single-component LipL32 and multi-component recombinant LipL32-41-OmpL1 vaccines against leptospira - Feng,C.Y. (2009)
Genes encoding lipoproteins LipL32, LipL41 and the outer-membrane protein OmpL1 of leptospira were recombined and cloned into a pVAX1 plasmid. BALB/c mice were immunized with LipL32 and recombined LipL32-41-OmpL1 using DNA-DNA, DNA-protein and protein-protein strategies, respectively. Prime immunization was on day 1, boost immunizations were on day 11 and day 21. Sera were collected from each mouse on day 35 for antibody, cytokine detection and microscopic agglutination test while spleen cells were collected for splenocyte proliferation assay. All experimental groups (N = 10 mice per group) showed statistically significant increases in antigen-specific antibodies, in cytokines IL-4 and IL-10, as well as in the microscopic agglutination test and splenocyte proliferation compared with the pVAX1 control group. The groups receiving the recombined LipL32-41-OmpL1 vaccine induced anti-LipL41 and anti-OmpL1 antibodies and yielded better splenocyte proliferation values than the groups receiving LipL32. DNA prime and protein boost immune strategies stimulated more antibodies than a DNA-DNA immune strategy and yielded greater cytokine and splenocyte proliferation than a protein-protein immune strategy. It is clear from these results that recombination of protective antigen genes lipL32, lipL41, and ompL1 and a DNA-protein immune strategy resulted in better immune responses against leptospira than single-component, LipL32, or single DNA or protein immunization.